2011
DOI: 10.1029/2011gc003606
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of magmas with bimodal crystal size and shape distributions: Insights from analog experiments

Abstract: [1] Magmas in volcanic conduits commonly contain microlites in association with preexisting phenocrysts, as often indicated by volcanic rock textures. In this study, we present two different experiments that investigate the flow behavior of these bidisperse systems. In the first experiments, rotational rheometric methods are used to determine the rheology of monodisperse and polydisperse suspensions consisting of smaller, prolate particles (microlites) and larger, equant particles (phenocrysts) in a bubble-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 45 publications
7
98
1
1
Order By: Relevance
“…To simulate natural melts, Mueller et al (2010) used silicone oil as a silicate melt analog, and art glitter, wollastonite, and angular silicone carbide grit as particles in the system. A similar study was recently presented by Cimarelli et al (2011), using a silicon oil as magma analog. Cimarelli et al (2011) modeled viscosity behavior as the suspension varied in volume, shape, and size.…”
Section: Relative Viscosity Determinationsmentioning
confidence: 92%
See 1 more Smart Citation
“…To simulate natural melts, Mueller et al (2010) used silicone oil as a silicate melt analog, and art glitter, wollastonite, and angular silicone carbide grit as particles in the system. A similar study was recently presented by Cimarelli et al (2011), using a silicon oil as magma analog. Cimarelli et al (2011) modeled viscosity behavior as the suspension varied in volume, shape, and size.…”
Section: Relative Viscosity Determinationsmentioning
confidence: 92%
“…A similar study was recently presented by Cimarelli et al (2011), using a silicon oil as magma analog. Cimarelli et al (2011) modeled viscosity behavior as the suspension varied in volume, shape, and size. In low particles concentration regions (Φ <0.2), they found that data derived from the approach were in good agreement with the experimental data.…”
Section: Relative Viscosity Determinationsmentioning
confidence: 92%
“…Considering those properties and approximations, using the models of Giordano et al (2008) for melt viscosity and Costa et al (2009) and Cimarelli et al (2011) for accounting for the effects of crystals, we estimated a reference effective magma viscosity of 108 Pa s. In our simplified model, the main effect of magma viscosity is on magma fragmentation depth as high viscosities tend to move fragmentation level at greater depths, because the critical volume fraction of bubbles is attained earlier upon magma ascent. Initial dyke thickness is assumed to be ∼100 m, consistent with typical values estimated for such magma viscosity (Wada, 1994).…”
Section: Control Of Local Stress Field On Eruption Dynamics and Intenmentioning
confidence: 99%
“…As an example, we report here a list of recent works which, embracing different techniques, have provided improvements in the following research fields: analytical [Metrich and Wallace 2008, Bachmann et al 2010, Blundy et al 2010, Mercier et al 2010, Metrich et al 2010, Edmonds et al 2013, experimental [Kueppers et al 2006, Ardia et al 2008Giordano et al 2008, Lavallée et al 2007, Caricchi et al 2011, Cimarelli et al 2011, Llewellin et al 2011, Martel 2012, Okumura et al 2013, Rivalta et al 2013, Polacci et al 2014, Kendrick et al 2014a, Wadsworth et al, 2014, Kendrick et al 2016, Kolzenburg et al 2016a, b, Russell and Giordano 2016Del Bello et al 2017], numerical [Costa et al 2007a, Maccaferri et al 2010, Longo et al 2012, de' Michieli Vitturi et al 2013, Melnik and Costa 2014 and observational volcanology [Kueppers et al 2005, Gurioli et al 2008, Andronico et al 2009, Gudmunsson et al 2012, Cashman et al 2013, Tuffen et al 2013, Gaudin et al 2016, volcano geophysics [Wright et al 2012a, Harris 2013, Ripepe et al 2013…”
Section: Introductionmentioning
confidence: 99%